"PULER" INNOVATION: PALM OIL MILL SOLID WASTE AS ORGANIC FERTILIZER TO SUPPORT SDG'S 12 - Ika Ucha Pradifta R; Tifany Zia Aznur; Saroha Manurung; Aulia Juanda; Mahyunis; Dina Arfianti Saragih; Delyana R Pulungan; Ritna Wahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Palm oil mill boiler ash is a solid industrial waste available in large quantities, but its utilization is still limited. This waste has alkaline properties and nutrient content that has the potential to improve the physical-chemical properties of tropical acid soils, such as pH, cation exchange capacity, and macronutrient availability, making it a potential sustainable soil ameliorant. This study aims to process organic fertilizer, namely an organomineral product based on boiler ash, with the aim of evaluating its chemical characteristics and assessing its potential application as a soil ameliorant. The analysis results show that Puler has a pH value of 9 and a nutrient composition that can improve soil quality without heavy metal concentrations above the Indonesian national standard threshold. These findings indicate that Puler can be an efficient alternative ameliorant and supports the utilization of palm oil industry waste. In addition, this puler also meets the criteria for organic fertilizer standards according to SNI 7763:2024